Ensuring Pain Relief for Children at the End of Life - Marie-Claude Grégoire; Gerri Frager (Pain Research and Management)
Pain management in the context of pediatric palliative care can be challenging. The present article reviews, through a case-based presentation, the nonpharmacological and pharmacological methods used to ensure adequate pain control in children facing end of life. Details on the impressive range of opioid dosages required and routes of administration are highlighted from published literature and clinical experience. Where available, evidence-based recommendations are provided. Potential side effects of pain medication and barriers to good pain control are discussed. Novel analgesics and innovative delivery methods are presented as future tools enhancing pain relief at the end of life. Some challenges to ethically grounded research in this important context of care are reviewed.